HEMODYNAMIC AND METABOLIC EFFECTS OF NEBIVOLOL IN LOCOMOTIVE CREW STAFF WITH NEWLY DIAGNOSED ARTERIAL HYPERTENSION - I. V. Osipova; O. N. Antropova; E. I. Bravkova; A. G. Zaltsman; T. B. Belousova; T. V. Perevozchikova; I. A. Batanina (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To evaluate influence of long-term monotherapy with nebivolol on blood pressure (BP) (office BP; self-monitoring BP, pre-trip BP monitoring, ambulatory BP monitoring (ABPM)) and metabolic blood profile in locomotive crew staff with newly diagnosed arterial hypertension (HT).Material and methods. Locomotive crew engineers and their assistants (n=50; age 20-55 y.o.) with newly diagnosed HT 1-2 degree with moderate-to-high cardiovascular risk were included into the open prospective uncontrolled study. The study duration was 12 months. The office BP level, heart rate were evaluated initially, in 12 weeks and 12 months of treatment; pre-trip BP level – one time per month; ABPM and blood biochemical tests (glucose and lipid profile) - initially and in 12 months of therapy. Data of BP self-monitoring, nebivolol treatment compliance and safety was also evaluated.Results. Long-term monotherapy with nebivolol allowed reaching the target level of office BP, self-monitoring BP, ABPM. Nebivolol provided BP control both in working days and in week end. Efficacy of nebivolol monotherapy was 88%. Nebivolol therapy improved basic ABPM indicators (load pressure, variability, daily rhythm), pulse BP, heart rate. Nebivolol had no significant negative metabolic effects, 78% of patients demonstrated sufficient compliance with nebivolol treatment. Adverse reaction (bradycardia) was observed in 2 (4%) patients.Conclusion. Nebivolol has high antihypertensive efficacy, metabolic neutrality and good safety profile in the locomotive crew staff with newly diagnosed HT.